MENGURANGI KEJENUHAN KERJA AKAN MENINGKATKAN KEPUASAN KERJA PARA AUDITOR DI BADAN PEMERIKSA KEUANGAN (BPK) - Jenia Putri Sumja; Sih Darmi Astuti (Lembaga Pengembangan Kinerja Dosen, 2021)
The purpose of this study is to examine the influence dual role conflict, burnout, and organizational justice on job satisfaction of the auditor employees in Badan Pemeriksa Keuangan (BPK) representatives of Central Java Province. Data were collected from questionnaires completed by 110 participants and analysed using Structural Equation Modeling (SEM), with AMOS 25.0 version. The findings reveal that dual role conflict had a psotive impact on job satisfaction. Further, burnout had a negative and significant on job satisfaction. Then organizational justice had a positive and significant impact on job satisfaction. Job satisfaction of Auditors at Badan Pemeriksa Keuangan (BPK) is most quickly achieved by reducing their burnout, followed by creating dual role conflict (functional), and creating organizational justice for them.